2016
DOI: 10.1614/ws-d-16-00050.1
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Crop and Weed Growth Responses to Arbuscular Mycorrhizal Fungi: Implications for Integrated Weed Management

Abstract: Integrated weed management (IWM) relies upon multiple chemical, physical, or biological weed management techniques to achieve an acceptable level of weed control. Agents that selectively suppress weeds but not crops and that can be manipulated in agriculture will be promising components for inclusion in IWM. We used a meta-analytic approach to investigate the potential of arbuscular mycorrhizal fungi (AMF) to contribute to IWM. We quantified the effect of crop and weed host status (strong and weak AMF hosts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 72 publications
1
9
0
Order By: Relevance
“…The current study is aimed at providing a quantitative review on how these management practices could influence the impact of cover crops on weed suppression through an analytical approach: meta-analysis. The adoption of metaanalysis for quantitative review is becoming more popular among agronomy researchers, as this approach provides a summarized quantitative estimate or information from data extracted through a comprehensive survey of previous studies (Egan et al, 2014;Pittelkow et al, 2015;Li et al, 2016;Himmelstein et al, 2017;Osipitan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The current study is aimed at providing a quantitative review on how these management practices could influence the impact of cover crops on weed suppression through an analytical approach: meta-analysis. The adoption of metaanalysis for quantitative review is becoming more popular among agronomy researchers, as this approach provides a summarized quantitative estimate or information from data extracted through a comprehensive survey of previous studies (Egan et al, 2014;Pittelkow et al, 2015;Li et al, 2016;Himmelstein et al, 2017;Osipitan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect facilitation through the soil microbial community has also been documented (Van der Heijden et al 1998;Bennett, Daniell and White 2013). A meta-analysis indicated that arbuscular mycorrhizal fungi can directly suppress weeds that are weak hosts for the fungi, but also can indirectly suppress some strong host weeds in the presence of strong host crops that ultimately obtain the advantage (Li et al 2016). These facilitative processes can differentially provide advantage to the weeds or crop in any given system at any particular time, so their interpretation must be made with caution and careful understanding of the drivers in variation before applying what appears to be a definitive outcome or assumption about the outcome of the interaction (e.g.…”
Section: Indirect Effects Of Competitionmentioning
confidence: 99%
“…Another factor influencing weed-crop competition dynamics is the function of arbuscular mycorrhizal fungi (AMF), which may increase the availability of immobile nutrients such as P (Harley 1989;Jeffries and Rhodes 1987;Stanley et al 1993) and improve crop yield (Zhang et al 2019). Most plants can host AMF, but several important weed species are characterized as weak or non-AMF hosts (Jordan et al 2000;Li et al 2016;Vatovec et al 2005). AMF can have a negative effect on the growth of these weed species, especially in the presence of a crop (Veiga et al 2011).…”
Section: Directions For Future Researchmentioning
confidence: 99%